Using titanium complexes to defeat cancer: the view from the shoulders of titans - Cini, Melchoir; Bradshaw, Tracey D.; Woodward, Simon (Royal Society of Chemistry, 2017)
When the first titanium complex with anticancer activity was identified in the 1970s, it was attractive, based on the presence of the dichloride unit in TiCl2Cp2 (Cp = η-C5H5)2, to assume its mode of biological action was closely aligned with cisplatin [cis-PtCl2(NH3)2]. Over the intervening 40 years however a far more complicated picture has arisen indicating multiple cellular mechanisms of cellular action can be triggered by titanium anti-cancer agents. This tutorial review aims to unpick the historical data and provide new researchers, without an explicit cancer biology background, a contemporary interpretation of both older and newer literature and to review the best techniques for attaining the identities of the biologically active titanium species and how these interact with the cancer cellular machinery.